Suicide: revision aspects neurobiological basis (Revista de Investigaciones Universidad del Quindío, 2021)
Review focusing on the issue of suicide, trying to search for the neurobiological basis for providing an explanation on there a sons by which individuals come to this threatening life extreme situation.The main foundations range from the influence of alcohol, relationship to cholesterol and serotonin receptors. In recent years, some approaches tried to identify a genetic factor to explain this health problem that is affecting mainly to Latin American countries. It is prevalent in women seeking for a solution to their problems; in adolescent populations (between 15 to 24 years) with increased susceptibility, and also in older men due to unemployment and divorce. This requires the participation of a multidisciplinary team to address this increasing public health problem.
Keywords: Suicide; neurobiological basis of suicide